2007
DOI: 10.1057/palgrave.jibs.8400319
|View full text |Cite
|
Sign up to set email alerts
|

On the growth of foreign affiliates: multinational plant networks, joint ventures, and flexibility

Abstract: We take a flexibility perspective to analyze employment growth in a large sample of Japanese manufacturing affiliates in nine Asian countries during the years leading up and into the Asian financial crisis (1995)(1996)(1997)(1998)(1999). We find that joint ventures are less flexible than wholly owned affiliates in responding to changing environmental conditions in the focal country and underperform in high growth environments. Multinational enterprises use the flexibility created by their multinational plant n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(12 citation statements)
references
References 93 publications
1
10
0
1
Order By: Relevance
“…Adner (2007) raised the notion of flexibility as reassignment of resources, noting that existing treatments of flexibility have largely focused on flexibility as redirection of activity and future research needs to look at flexibility through reallocation of resources. Similarly, treatments of flexibility in global strategy research have emphasized the flexibility advantage from shifting value chain activities from a country experiencing adverse changes to a more favorable country within the MNE's network (Belderbos and Zou, 2007;Chung et al, 2010). Whereas case studies suggest that MNEs such as GM and Qantas engage in reallocation by releasing resources from existing activities and redeploying them to new opportunities (Maitland and Sammartino, 2012), we identify investment purpose diversity as a potential lens through which to study such reallocations.…”
Section: Discussionmentioning
confidence: 94%
“…Adner (2007) raised the notion of flexibility as reassignment of resources, noting that existing treatments of flexibility have largely focused on flexibility as redirection of activity and future research needs to look at flexibility through reallocation of resources. Similarly, treatments of flexibility in global strategy research have emphasized the flexibility advantage from shifting value chain activities from a country experiencing adverse changes to a more favorable country within the MNE's network (Belderbos and Zou, 2007;Chung et al, 2010). Whereas case studies suggest that MNEs such as GM and Qantas engage in reallocation by releasing resources from existing activities and redeploying them to new opportunities (Maitland and Sammartino, 2012), we identify investment purpose diversity as a potential lens through which to study such reallocations.…”
Section: Discussionmentioning
confidence: 94%
“…The various streams of research on multinational firms have identified many other reasons why firms seek to undertake multinational investment, assume smaller or larger equity shares, and make greater or less use of expatriates (see Caves, 1996 for a review). For instance, while having greater equity share facilitates the coordination of switching options and operating flexibility, it can reduce firms' growth option values (e.g., Belderbos and Zou, 2007;Chi and McGuire, 1996;Tong et al, 2008). Furthermore, although firms might be choosing investment strategies to reduce downside risk, the difficulty to predict changes in country environments such as labor cost movements may still lead firms to end up having a suboptimal portfolio in terms of executing switching options and reducing downside risk.…”
Section: Supplementary Analysesmentioning
confidence: 99%
“…Actually, and relying on the way of thinking about foreign direct investment (FDI) enriched by real option theory (Campa, 1993;Li & Rugman, 2007), foreign firms may decide to switch operations quickly between locations in response to changing costs differentials, market opportunities and host country uncertainty, particularly (Belderbos & Zou, 2009). Unless sunk costs and the irreversibility of investment are considerable -which may, in opposition, create some ''hysteresis'' and inertia in foreign firms' strategic response to macroeconomic changes -multinational firms tend to be more footloose than their domestic counterparts when facing environmental uncertainty, especially when their real investment options are redundant, either at the host-country level or at the MNE portfolio level (Belderbos & Zou, 2007, 2009Ghosal, 2010;Lehmann, 2002).…”
Section: Footloose Multinationals and Economic Downturnsmentioning
confidence: 99%